What is Gone? Moral Dilemma, Moral Choice and Moral Act in Gone Baby Gone - Arıkan, Seda (Serdar ÖZTÜRK, 2020)
The film adaptation of Dennis Lehane’s novel Gone Baby Gone (Ben Affleck, 2007) is based on a moral questioning about right choice and right act although, on the surface, it appears as a detective film in which the mystery is unexpectedly uncovered by discovering the “good criminal”. The obligation to make a moral choice in case of a moral dilemma results in the conflicted moral attitudes of the characters, which invites the spectator to question the validity of each. In the film, the basic moral choice that should be made by the characters is whether to take an abducted little girl back to her careless, and also drug user mother, or to let her stay with her abductor, but a respectful police captain who grants a promising future for her. The matter becomes much more problematic when the characters adopt contradictory moral attitudes varying from moral absolutism to moral subjectivism, two opposite poles, and also including moral objectivism, which could be accepted as a moderate breeze between them. In this sense, this study examines how moral dilemmas, exercising their influence over the spectator as well, reveal various moral attitudes that have been essentially discussed in the history of philosophy on the basis of the choices made by the characters. The study, analyzing Gone Baby Gone in terms of moral dilemma, choice and act, aims to trace what is gone –namely what is left behind by the choice, or the moral would-be possibilities as they were not chosen– within the context of moral philosophy.
Keywords: Philosophy; Felsefe